Analysis of Nero’s Insecurities in the Devil May Cry Series - Kenny Gian Thong; Nugraheni Widianingtyas (English Language and Education Spectrum, 2023)
In the entirety of human life, the feeling of insecurity has always occurred, even in fictional works. However, little is known about the study of insecurity in a character in a video game series. Therefore, this study is to analyze the insecurity of Nero, a protagonist of the Devil May Cry series gives insights on what are the causes and the types of his insecurities, and finds the true nature of Nero’s insecurity and how he deals with it. Data for the study comprised psychological research on insecurity and its causes, as well as the story of Nero. The data were transcribed and analyzed in qualitative research. The findings revealed that Nero developed his insecurities ever since he was left alone at the orphanage doorstep, being bullied by other children, the death of his adoptive brother, and being insulted by his mentor. As such, Nero develops the tendencies of being impulsive and brash whenever people he loved are in danger, as well as being arrogant and rebellious. The study also revealed that in order to deal with his insecurities, Nero seeks more power and validation that he is indeed capable of saving other people, and he is not powerless.